Kriteria Wajib Zakat (Muzaki) dan Penerima Zakat (Mustahik) - Ali Murtadho Emzaed; Ilham Perdana Akbar; Muhammad Afriza Rifandy; Ahmad Arif Setiawan; Syaifullah Syaifullah (STIKes Ibnu Sina Ajibarang, 2025)
Zakat is one of the pillars of Islam that must be fulfilled by every Muslim who meets specific conditions. Linguistically, zakat means “clean,” “pure,” “fertile,” and “blessed,” while in Islamic terminology, zakat refers to a specific portion of wealth that must be given to those who are entitled to receive it according to Islamic law. Zakat serves both social and spiritual purposes, namely purifying wealth and the soul, as well as reducing social inequality within society. There are various types of zakat, such as zakat al-fitr and zakat on wealth (zakat al-mal). Through the proper implementation of zakat, it is hoped that economic justice, social solidarity, and the overall welfare of the Muslim community can be achieved.